Population growth demand and challenges of health equality among immigrants towards healthcare services in Malaysia - Muhammad Qusyairi Fakuruddin,; Nor Aliya Ayub,; Nor Azila Muhd Aris,; Nur Atiqah Mohd Ahwan,; Siti Bazlina Mohd Rawi,; Rosnah Sutan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaysia's economic development increases the demand for immigrant workers to ensure health equality. To achieve Universal Health Coverage, issues related to immigrants need to be revisited. A narrative review was conducted on specific scopes of health access barriers among immigrants from Scopus, PubMed, Web of Science, and Google Scholar. Immigrants face health inequalities due to complex immigration policies, cultural and social adaptation differences, language barriers, financial constraints, and low literacy awareness of healthcare systems. This brief essay highlights challenges for immigrants adhering to Malaysia’s Health White Paper strategies in meeting Universal Health Coverage. Expanding these strategies is vital to uphold immigrants’ fundamental rights and ensure health equality among the minority group of the population.